Theoretical analysis of the impacts of light illumination on the transient current of sputter-deposited non-doped ZnO films - Omura, Yasuhisa; Sato, Shingo (AIP Advances, 2021)
This paper proposes a possible theoretical model to analyze the impacts of light illumination on the post-illumination transient current of sputter-deposited non-doped ZnO films. Although the authors have already demonstrated experimentally the impact of wavelength on the resistance of such films (various light-emitting diodes were used), the influence of ambient gas on their resistance, and the influence of temperature on resistance in detail, no significant theoretical basis was provided. In this paper, the physical images of the phenomena are theoretically reconsidered and a theoretical model is developed based on the experimental results. The mathematical formulation provided involves the time-dependent diffusion current model, and the continuity equation is solved to achieve a plausible solution of the time constant of the transient process. The theoretical solution strongly suggests that oxygen vacancy levels and/or traps around the grain boundaries and inside the grains contribute to the post-illumination transient behavior of dc-biased current. The non-linear effect on the transient process is also discussed for directing future research.